Negara Pancasila: Inspirasi Model Negara Islam Kontemporer Berbasis Tafsir Maqaṣidi - L Lufaefi (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2019)
One of the debates among Muslims which until now has not ended is about the state model in Islam. Islamic leaders who are concerned about the issue, such as Rashid Ridha, Imam Al-Mawardi, Taqī Al-Dīn Al-Nabhāni, Alī Abd Al-Rāziq, Nurcholis Madjid and Hasyim Muzadi, have significant differences of opinion. The difference is not only led to debate in the intellectual world, but also physically at the lower level. This paper discusses and analyzes the state model of Pancasila with its relation to the Qur’anic verses about the state. With the analysis of Maqāṣid Alquran, the state of Pancasila is an ideal contemporary Islamic state. Through its five principles, the Pancasila state discovered the essence of an Islamic state capable of delivering the objectives of Islamic law and unity in diversity. Therefore it can be accepted by Indonesian people whose population is plural and its Muslim population occupies the largest position in the world, and is the inspiration of other countries in the world.